Development of A Decahedral Nanoenzyme Capable of Overcoming Hypoxia to Facilitate the Iodine-125 Radiosensitization of Esophageal Cancer - Jiao, Dechao; Wu, Kunpeng; Xu, Kaihao; Liu, Yiming; Zhao, Deyao; Han, Xinwei; Fan, Ruitai (Frontiers in Bioengineering and Biotechnology, 2021)
Radioisotopes have long been leveraged for internal radiotherapy-mediated cancer treatment. However, such therapeutic approaches are associated with serious side effects, and their efficacy is limited by intratumoral hypoxia. Herein, we prepared a folic acid-decorated palladium decahedral platform capable of enhancing the radiotherapeutic efficacy of iodine-125 (125I) seed treatment. This decahedral nanoenzyme was able to target tumor regions and catalyze the conversion of intracellular H2O2 to O2, thereby alleviating hypoxia within the tumor microenvironment. In addition, palladium was hypoxia can be alleviated, on the other hand, palladium was able to enhance the radiotherapeutic energy deposition within tumor tissues. The results of this analysis indicated that synthesized decahedral constructs can efficiently target and modify the hypoxic tumor microenvironment while simultaneously enhancing radiation energy deposition therein. Relative to palladium nanodots, the prolonged in vivo circulation of these decahedral constructs better enabled them to facilitate sustained radiosensitization. Overall, the results of this study highlight a novel approach to improving the therapeutic utility of 125I seed interstitial implantation, thus underscoring an important direction for future clinical research.